2014
DOI: 10.1108/jmp-07-2012-0231
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and behaviors of Hispanic workers: a review

Abstract: Purpose – The purpose of this paper is to summarize research about Hispanic workers in the USA and identifies directions for future research. Design/methodology/approach – The paper identifies, analyze, and summarize 112 peer reviewed publications that deal with Hispanic workers in the USA. Findings – The findings are grouped into major categories that deal with prejudice, discrimination, and diversity; job-related attitudes and behaviors; job search and careers; the interface with gender, sexual hara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 111 publications
(202 reference statements)
0
17
0
Order By: Relevance
“…Latinos/as tend to share a common set of values that are different from those found in mainstream American culture, such as higher levels of in-group collectivism, greater acceptance of hierarchical power structures, and stronger adherence to traditional gender roles (59, 60). For instance, familism (i.e., a strong attachment to nuclear and extended family) is a central value among Latinos/as that may influence OSH behaviors (60).…”
Section: Resultsmentioning
confidence: 99%
“…Latinos/as tend to share a common set of values that are different from those found in mainstream American culture, such as higher levels of in-group collectivism, greater acceptance of hierarchical power structures, and stronger adherence to traditional gender roles (59, 60). For instance, familism (i.e., a strong attachment to nuclear and extended family) is a central value among Latinos/as that may influence OSH behaviors (60).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the healthy migrant worker hypothesis, while interpreting the findings of this study, we should also consider other factors that could explain the findings in relation to the well-being of migrant workers. Perceptions of health and well-being are subjective and include aspects of the cultural background, such as behaviors, norms, values and experiences which can help explain these divergences [45][46][47]. Thus, whereas workload was found to be related to well-being in both subsamples, social support and job insecurity were only found to have a relationship with well-being in the native, and not in the migrant, sample.…”
Section: Discussionmentioning
confidence: 93%
“…These back-of-house jobs are often difficult and 78 IHR 32,1 dangerous due to the strength of the commercial cleaning chemicals and heavy equipment, combined with needing to maintain a fast pace during the time constraints of an employee shift. Studies have identified an unacceptable range of discrimination, exploitation and harassment by employers but economic necessity and Latino cultural values push them to be resilient by adapting to their adverse work circumstances (Eggerth et al, 2012;Guerrero and Posthuma, 2014;Shinnar, 2007;Valdivia and Flores, 2012).…”
Section: Translating Emotional Insightsmentioning
confidence: 99%